MSME Financial Risk Analysis (Case Study at Aneka Ragam UD in Panca Mukti Hamlet) - Cindy Rahayu; Muhammad Raihan Nur Faizi; Robby Alvido Silaen; Tamara Alvio Dana Damanik; Yosia Arianta Purba; Rossy Pratiwy Sihombing (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the key factors for the success of a company is financial income. Every company wants optimal financial performance, so does MSME. However, MSMEs face a problem that causes risks that can hinder the journey of a business. With this research, it is hoped that it can help find solutions to the financial problems faced by UD Aneka Ragam. This study aims to identify risks that can reduce MSME financial income. Qualitative approaches and survey data collection methods are used to obtain financial data to complement primary and secondary data. The results of the study show that UD Aneka Ragam has several risks that can cause financial decline.